Reproductive factors and non-Hodgkin lymphoma risk in the California Teachers Study. - Jennifer Prescott; Yani Lu; Ellen T Chang; Jane Sullivan-Halley; Katherine D Henderson; Christina A Clarke; Huiyan Ma; Claire Templeman; Dennis Deapen; Leslie Bernstein (PLoS ONE)
Background Non-Hodgkin lymphoma (NHL) is a malignancy etiologically linked to immunomodulatory exposures and disorders. Endogenous female sex hormones may modify immune function and influence NHL risk. Few studies have examined associations between reproductive factors, which can serve as surrogates for such hormonal exposures, and NHL risk by subtype. Methodology/principal findings Women in the California Teachers Study cohort provided detailed data in 1995-1996 on reproductive history. Follow-up through 2007 identified 574 women with incident B-cell NHL. Hazard rate ratios (RR) and 95% confidence intervals (CI) were estimated using Cox proportional hazards models to assess associations between reproductive factors and all B-cell NHL combined, diffuse large B-cell lymphomas, follicular lymphomas, and B-cell chronic lymphocytic leukemias/small lymphocytic lymphomas. Pregnancy was marginally associated with lower risk of B-cell NHL (RR = 0.84, 95% CI = 0.68-1.04). Much of the reduction in risk was observed after one full-term pregnancy relative to nulligravid women (RR = 0.75, 95% CI = 0.54-1.06; P for trend <0.01), particularly for diffuse large B-cell lymphomas (P for trend = 0.13), but not among women who had only incomplete pregnancies. Age at first full-term pregnancy was marginally inversely associated with B-cell NHL risk overall (P for trend = 0.08) and for diffuse large B-cell lymphomas (P for trend = 0.056). Breast feeding was not associated with B-cell NHL risk overall or by subtype. Conclusions Full-term pregnancy and early age at first full-term pregnancy account for most of the observed reduction in B-cell NHL risk associated with gravidity. Pregnancy-related hormonal exposures, including prolonged and high-level exposure to progesterone during a full-term pregnancy may inhibit development of B-cell NHL.